Analysis of the Aflatoxin M1 contamination in traditional and commercial cheeses consumed in Yemen. (5th November 2021) - Abdullah Murshed, Safwan Ahmad; Rizwan, Muhammad; Akbar, Fazal; Zaman, Nasib; Suleman, Muhammad; Shujait Ali, Syed
Abstract : The current study aimed to determine the levels of Aflatoxin M1 in traditional Taizi cheese and commercial cheeses utilised in Yemen. A total of 273 cheese samples were collected from supermarkets and analysed for AFM1 contamination by enzyme‐linked immunosorbent assay (ELISA) and high‐performance liquid chromatography (HPLC). Among these samples, 79.12% were positive for AFM1 contamination with levels ranging from 0.020 to 5.955 μg/kg. AFM1 was detected at 84.67 and 73.53% in commercial and traditional cheeses, respectively. In the current study, 32.6% of the total cheese samples were contaminated with AFM1 at a level above the acceptable limit (0.250 μg/kg) of the European Commission. Results of this study revealed that the presence of AFM1 contamination in different types of cheese samples should be considered a serious public health problem in Yemen. Abstract : Cheese samples were collected from supermarkets in order to determine the levels of aflatoxin M1. AFM1 contamination was analysed by enzyme‐linked immunosorbent assay (ELISA) and high‐performance liquid chromatography (HPLC). The figure shows AFM1 in different types of cheese samples analysed by HPLC and ELISA. Among these samples, 79.12% were positive for AFM1 contamination with levels ranging from 0.020 to 5.955 μg/kg. AFM1 was detected at 84.67 and 73.53% in commercial and traditional cheeses, respectively. In the current study, 32.6% of the total cheese samples were contaminated with AFM1 at level above the acceptable limit (0.250 μg/kg) of the European Commission.